2012
DOI: 10.1182/blood-2011-11-393983
|View full text |Cite
|
Sign up to set email alerts
|

Necdin, a p53 target gene, regulates the quiescence and response to genotoxic stress of hematopoietic stem/progenitor cells

Abstract: We recently defined a critical role for p53 in regulating the quiescence of adult hematopoietic stem cells (HSCs) and identified necdin as a candidate p53 target gene. Necdin is a growth-suppressing protein and the gene encoding it is one of several that are deleted in patients with Prader-Willi syndrome. To define the intrinsic role of necdin in adult hematopoiesis, in the present study, we transplanted necdin-null fetal liver cells into lethally irradiated recipients. We show that necdin-null adult HSCs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 47 publications
4
67
0
Order By: Relevance
“…This approach is based on the hypothesis that prior attempts to expand HSCs ex vivo using serum-containing (SC) media and cytokine combinations actually result in the silencing of HSC genetic programs (2,7,9,17,(26)(27)(28)(29)(30)(31). This alternative strategy is consistent with the growing evidence that epigenetic mechanisms play important roles in determining whether an HSC undergoes symmetrical divisions and generates additional stem cells, asymmetrical divisions that at best maintain HSC numbers while generating hematopoietic progenitor cells (HPCs), or symmetrical commitment divisions that deplete HSC numbers and generate greater numbers of HPCs (26,27,(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 57%
“…This approach is based on the hypothesis that prior attempts to expand HSCs ex vivo using serum-containing (SC) media and cytokine combinations actually result in the silencing of HSC genetic programs (2,7,9,17,(26)(27)(28)(29)(30)(31). This alternative strategy is consistent with the growing evidence that epigenetic mechanisms play important roles in determining whether an HSC undergoes symmetrical divisions and generates additional stem cells, asymmetrical divisions that at best maintain HSC numbers while generating hematopoietic progenitor cells (HPCs), or symmetrical commitment divisions that deplete HSC numbers and generate greater numbers of HPCs (26,27,(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 57%
“…Only recently it was shown that p53 and its target Nectin promoted quiescence of murine HSCs. Loss of p53 led to increased cell cycle entry and a significant increase in LSK cell numbers [143][144][145]. While exit from quiescence was associated with loss of HSC self-renewal and impaired performance in competitive transplantation assays in many genetically modified mice, deficiency of p53 was shown to result in a better engraftment into recipient mice.…”
Section: The Role Of P53 Beyond Dna Damage Responsementioning
confidence: 99%
“…52 Recent mouse studies have also confirmed that Necdin-null adult HSCs are less quiescent and more proliferative than normal. 109 Other targets modulated by p53 during differentiation of HSCs remain to be identified.…”
Section: Role Of P53 Downstream Targets In Hematopoiesismentioning
confidence: 99%